2021
DOI: 10.1007/s11517-021-02437-4
|View full text |Cite
|
Sign up to set email alerts
|

GLYFE: review and benchmark of personalized glucose predictive models in type 1 diabetes

Abstract: Due to the sensitive nature of diabetes-related data, preventing them from being shared between studies, progress in the field of glucose prediction is hard to assess. To address this issue, we present GLYFE (GLYcemia Forecasting Evaluation), a benchmark of machine-learning-based glucose-predictive models.To ensure the reproducibility of the results and the usability of the benchmark in the future, we provide extensive details about the data flow. Two datasets are used, the first comprising 10 insilico adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 101 publications
0
24
0
Order By: Relevance
“…When we compare the results on our dataset to the literature, we note that we do not reach the performance of comparable models on the OhioT1DM dataset ( 4 ) consisting of much longer time series per participant (8 weeks) and comprising only adults. In a recent benchmark ( 9 ), including deep learning and non-deep learning architectures, an LSTM was among the best-performing methods, reaching an RMSE of around 1.12 for a prediction horizon (PH) of 30 min and an RMSE of 2.64 for PH equal to 120 min. 3 Further, the reference measure for the OhioT1DM dataset was reported to be 1.57 and 3.20 for PH equal to 30 and 120 , which is much lower than for our dataset—indicating that the prediction task is harder for our dataset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When we compare the results on our dataset to the literature, we note that we do not reach the performance of comparable models on the OhioT1DM dataset ( 4 ) consisting of much longer time series per participant (8 weeks) and comprising only adults. In a recent benchmark ( 9 ), including deep learning and non-deep learning architectures, an LSTM was among the best-performing methods, reaching an RMSE of around 1.12 for a prediction horizon (PH) of 30 min and an RMSE of 2.64 for PH equal to 120 min. 3 Further, the reference measure for the OhioT1DM dataset was reported to be 1.57 and 3.20 for PH equal to 30 and 120 , which is much lower than for our dataset—indicating that the prediction task is harder for our dataset.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce hyper-or hypoglycemic excursions, reliable prediction of future blood glucose levels from previous measurements is desirable for children, as well as adults with T1D. Since the release of the OhioT1DM dataset (4), which consists of data of 6, and later 12 (5) adults with T1D, the topic of blood glucose forecasting has been picked up by the machine learning community (6)(7)(8)(9)(10). For example, McShinsky and Marshall (7) investigated the performance of classical non deep-learning based methods such as autoregressive moving average (ARIMA), random forests, and support vector machines (SVM) for forecasting blood glucose values.…”
Section: Introductionmentioning
confidence: 99%
“…21 Autoregressive with exogenous inputs is a good reference model since it has been used in many studies in the diabetes literature. Moreover, the choice of SVR models was motivated by the fact that among ML methods SVR has demonstrated promising clinical acceptability, 33 whereas LSTM, designed with the same architecture as the LSTM section of the proposed CNN-LSTM model, allows us to demonstrate the advantage of the added convolutional layers for prediction. In addition, since CRNN, which is comprised of three convolutional and one LSTM layer, and its modifications has shown promising results in various studies, 21,34 we implemented it based on the code repository provided in.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…As a consequence, the models are trained on maximizing the accuracy of the predictions. However, in the benchmark study we recently conducted [13], we showed that a good accuracy does not ensure that the predictions are clinically acceptable. Indeed, some errors, despite their relatively low magnitude, can be very dangerous for the patient (e.g., errors in the hypoglycemia region).…”
Section: Introductionmentioning
confidence: 91%